Developing and promoting a highland community livelihood for sustainable tourism: The case of Kg. Bundutuhan, Ranau, Sabah - Toh, Pei Sung; Awangku Hassanal Bahar Pengiran Bagul,; Justin Sentian,; Ramzah Dambul, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Located right at the foot of Mt. Kinabalu but 1,200 m above sea-level the challenge of developing and promoting sustainable tourism in Kg. Bundu Tuhan is formidable. The most crucial is identifying existing tourism assets (both tangible and non-tangible) and converting them into profitable business which are aggravated by a glaring lack of knowledge and skills in business management and marketing strategy. This study seeks to determine existing viable tourism assets of village and to establish a conceptual framework on how to develop these assets. The study employs qualitative approaches, such as the use of case studies and surveys. This paper outlines the findings of the ground investigation, which are: (i) the identification of existing tourism assets; (ii) the establishment of preferred mechanisms in turning the assets into business; and (iii) the development of conceptual model for capacity building for the community based on the items identified in (i) and (ii). This paper concludes the study by recommending that a successful implementation of the outcome of the capacity building (the actual execution of the projects) that could lead to the equitable distribution of benefits and opportunities among stakeholders and could improve the well-being of the local community.